Effects of Different Gasoline Additives on Fuel Consumption and Emissions in a Vehicle Equipped With the GDI Engine - Wen, Mingsheng; Yin, Zenghui; Zheng, Zunqing; Liu, Haifeng; Zhang, Chuanqi; Cui, Yanqing; Ming, Zhenyang; Feng, Lei; Yue, Zongyu; Yao, Mingfa (Frontiers in Mechanical Engineering, 2022)
The use of fuel additives is considered as a simple and cost-effective approach to improve combustion, increase fuel efficiency and reduce harmful emission of internal combustion (IC) engines by changing specific properties of fuels without additional devices or IC engines structure modification. In this study, five unconventional gasoline additives, i.e., isopropyl ether, aniline, diethylamine, dimethyl malonate and p-tert-butylphenol, were blended in the baseline gasoline (G92), and the five blended fuels are referred to as G92-1, G92-2, G92-3, G92-4 and G92-5, respectively. The fuels with different additives were tested on a compact passenger vehicle with a 1.4-liter turbocharged gasoline direct injection engine to evaluate their effects on performance and emissions, and the G92 gasoline was compared as baseline. The new European drive cycle was chosen in the tests. The experimental results show little or slight improvement in fuel consumption for fuels blended with additives. Regarding to conventional gas emissions, the lowest NOx, CO, THC, and CO2 emissions were achieved when fueling G92-5 (blending with p-tert-butylphenol), G92-2 (blending with aniline), G92-3 (blending with diethylamine), and G92-3 (blending with diethylamine) fuels, respectively. Compared with the baseline gasoline fuel, all the fuels with additives show improved engine-out PM emissions and acceleration performance slightly.